Identifikasi Bahaya dan Pengendalian Risiko Kecelakaan Kerja Menggunakan Metode HIRARC (Hazard Identification, Risk Assesment, Risk Control) Pada Industri Pengolahan Hasil Perikanan - Amalia, Wahyuni; Mufti, Wahyu Fitrianda; Alfiza, Sepno (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
PT XBY is a company that processes fishery products into frozen food. In the production area, there was a work accident that resulted in injury. The purpose of this study was to identify potential hazards in the work area and control the risk of work accidents. The method used is HIRARC, which is to identify, assess, and control the risk of work accidents. There were 13 cases of potential hazards recorded with details of the risk level, namely 5 cases (38%) were classified as low risk, 4 cases (31%) were classified as medium risk, 3 cases (23%) were classified as high risk and 1 case (8%) was categorized as extreme risk. Based on the potential hazards, the controls that must be carried out are to use PPE in accordance with the SOP, install the Hazard symbol in the workplace, add tools to lift fish meat to the mixer machine, create a special forklift lane and carry out regular maintenance on the cold storage machine and surimi freezer machine.